2023
DOI: 10.1097/ta.0000000000004103
|View full text |Cite
|
Sign up to set email alerts
|

Damage control resuscitation in adult trauma patients: What you need to know

Danny T. Lammers,
John B. Holcomb

Abstract: Death after injury is a worldwide epidemic. Hemorrhage as a cause of death represents the leading potentially preventable condition. Based on hard-won experience from the recent wars, and two decades of military and civilian research, damage-control resuscitation (DCR) is now widely used. This article will briefly describe the history of blood transfusion, outline “why we do DCR,” and then discuss “how we do DCR.” Modern DCR occurs both prehospital and in the hospital and has several main tenants. Currently, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Meanwhile, we recommend the early reversal of anticoagulant/antiplatelet agents in tSCI polytrauma patients needing interventions for life-threatening hemorrhage or emergency spinal surgery. Massive transfusion is frequently utilized in bleeding trauma patients [ 14 , 40 ]. The pragmatic randomized optimal platelet and plasma ratios (PROPPR) study, involving 680 trauma patients with major bleeding, was performed to determine the safety and the effectiveness of a transfusion strategy involving plasma, PLTs and RBCs in a 1:1:1 ratio compared with a 1:1:2 ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, we recommend the early reversal of anticoagulant/antiplatelet agents in tSCI polytrauma patients needing interventions for life-threatening hemorrhage or emergency spinal surgery. Massive transfusion is frequently utilized in bleeding trauma patients [ 14 , 40 ]. The pragmatic randomized optimal platelet and plasma ratios (PROPPR) study, involving 680 trauma patients with major bleeding, was performed to determine the safety and the effectiveness of a transfusion strategy involving plasma, PLTs and RBCs in a 1:1:1 ratio compared with a 1:1:2 ratio.…”
Section: Discussionmentioning
confidence: 99%
“…10,30 A growing body of literature has recommended the use of different pathophysiologic parameters ("holistic physiologic status"). 13,40 Among those is the description of the so-called "diamond of death," which includes acidosis, hypothermia, coagulopathy, and hypocalcemia. 41 The present study showed improved prediction of outcomes when both the anatomic injury distribution and a holistic pathophysiologic approach were applied.…”
Section: Extremity Injuriesmentioning
confidence: 99%
“…Mortality rates in children with severe bleeding from trauma or medical etiologies range between 36% and 60%, 1 whereas in adults with trauma it ranges between 20% and 24% 2 . Death from traumatic hemorrhage is the most common preventable cause of death after injury due to inadequate or delayed care 3–6 …”
Section: Introductionmentioning
confidence: 99%
“…In the United States, these blood products are administered in either a balanced ratio of blood components or with low titer group O whole blood (LTOWB) 7–10 . Based on emerging evidence that demonstrates potential efficacy and safety, LTOWB is now utilized in over 300 US trauma centers in both adults and children with hemorrhagic shock 5,6,11 . Studies in adults and children indicate an independent association with improved 24‐hour or 28‐day survival 12–16 …”
Section: Introductionmentioning
confidence: 99%